Sustainable Development in Rural China: Field Survey and Sino-Japan Comparative Analysis - Qin, Bingtao (Springer, 2015)
The book provides a study of sustainable development in rural China. Because of its huge population and vast land area, this is an important issue not only for China but for the whole world. The research presented is both multi aspect and systematical. It can be likened to a tree where the trunk is the three main aspects: economy, environment and rural society, and the five main branches are agricultural development, industrial pollution, energy security, labor migration and social welfare, and these are the book’s five main topics. The research methods of field survey and Sino-Japanese comparison will be of particular interest to readers. The field survey enables readers to become familiar with the environment of rural China. Survey reports and data provide readers with a more profound and vivid understanding of rural China and comparative methods benefit readers from different countries and a variety of cultural backgrounds. For Japanese readers or readers who understand Japanese well, they make China more easily understandable, while Chinese readers gain insights into the country’s future and the direction of current developments based on a Japanese frame of reference. For readers outside China and Japan, this book serves as an introduction to Chinese society and also to Japan. Finally, the author provides various paradigmatic scenarios, including default and sustainable. After reading this book, readers will be aware that the earlier and the more we pay attention to these issues, the easier it will be for rural China to achieve a sustainable situation.